How would you show that #f (x) = 7x +3# and #f^-1(x) = (x +3 )/ 7# are inverses of each other?

Answer 1

To show that ( f(x) = 7x + 3 ) and ( f^{-1}(x) = \frac{x + 3}{7} ) are inverses of each other, we need to verify that ( f(f^{-1}(x)) = x ) and ( f^{-1}(f(x)) = x ) for all ( x ) in their respective domains.

Let's first find ( f(f^{-1}(x)) ): [ f(f^{-1}(x)) = f\left(\frac{x + 3}{7}\right) = 7\left(\frac{x + 3}{7}\right) + 3 = x + 3 ]

Now, let's find ( f^{-1}(f(x)) ): [ f^{-1}(f(x)) = f^{-1}(7x + 3) = \frac{7x + 3 + 3}{7} = x ]

Since both ( f(f^{-1}(x)) ) and ( f^{-1}(f(x)) ) simplify to ( x ), we can conclude that ( f(x) ) and ( f^{-1}(x) ) are inverses of each other.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Verify that #f^(-1)(x) = (x-3)/7# not #(x+3)/7#

These functions are not inverses of one another.

The correct formula for #f^(-1)(x)# can be written:
#f^(-1)(x) = (x-3)/7#

In fact the variable name used does not matter, so I will write:

#f^(-1)(y) = (y-3)/7#
Then substituting #y=f(x)# we find:
#f^(-1)(f(x)) = (f(x)-3)/7 = ((7x+3)-3)/7 = (7x)/7 = x#
Substituting #x=f^(-1)(y)# we find:
#f(f^(-1)(y)) = 7f^(-1)(y)+3 = 7((y-3)/7)+3 = (y-3)+3 = y#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7